Recent advances in the study of anesthesia-and analgesia-related mechanisms of S-ketamine - Zhou, Jian-shun; Peng, Guan-fa; Liang, Wei-dong; Chen, Zhen; Liu, Ying-ying; Wang, Bing-yu; Guo, Ming-ling; Deng, Yun-ling; Ye, Jun-ming; Zhong, Mao-lin; Wang, Li-feng (Frontiers in Pharmacology, 2023)
Ketamine is a racemic mixture of equal amounts of R-ketamine and S-ketamine and is well known to anesthesiologists for its unique dissociative anesthetic properties. The pharmacological properties of ketamine, namely, its sympathetic excitation, mild respiratory depression, and potent analgesia, are still highly valued in its use as an anesthetic for some patients. In particular, since its advent, Sketamine has been widely used as an anesthetic in many countries due to its increased affinity for NMDA receptors and its enhanced anesthetic and analgesic effects. However, the anesthetic and analgesic mechanisms of S-ketamine are not fully understood. In addition to antagonizing NMDA receptors, a variety of other receptors or channels may be involved, but there are no relevant mechanistic summaries in the literature. Therefore, the purpose of this paper is to review the mechanisms of action of S-ketamine on relevant receptors and systems in the body that result in its pharmacological properties, such as anesthesia and analgesia, with the aim of providing a reference for its clinical applications and research.